Communicating Two States in Perovskite Revealed by Time-Resolved Photoluminescence Spectroscopy. Issue 1 (December 2018) - Chen, Yanwen; Wang, Tianmeng; Li, Zhipeng; Li, Huanbin; Ye, Tao; Wetzel, Christian; Li, Hanying; Shi, Su-Fei
Abstract Organic-inorganic perovskite as a promising candidate for solar energy harvesting has attracted immense interest for its low-cost preparation and extremely high quantum efficiency. However, the fundamental understanding of the photophysics in perovskite remains elusive. In this work, we have revealed two distinct states in MAPbI3 thin films at low temperature through time-resolved photoluminescence spectroscopy (TRPL). In particular, we observed a photo-induced carrier injection from the high energy (HE) state to the low energy (LE) state which has a longer lifetime. The strong interaction between the two states, evidenced by the injection kinetics, can be sensitively controlled through the excitation power. Understanding of the interacting two-states not only sheds light on the long PL lifetime in perovskite but also helps to understand the different behavior of perovskite in response to different excitation power. Further efforts in modifying the low energy state could significantly improve the quantum efficiency and lead to novel application in optoelectronics based on perovskite.